Microbial Spectrum and Resistance Patterns in Peritoneal Fluid of Patients with Hollow Viscus Perforation - Dr Aishwarya Suhas Kulkarni, Dr S D Mandolkar, Dr Asif (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hollow viscus perforation leadingto secondary peritonitis is a common abdominalemergency in low- and middle-income countries.The outcome relies heavily on timely surgery andappropriate early antibiotic treatment. However,standard antibiotic regimens may not reflect thelocal microbial flora and resistance patterns.